OPTIMALISASI LAYANAN TERPADU UNTUK PERTUMBUHAN INVESTASI DI KOTA KENDARI - La Ode Muhammad Elwan; Taufik; Dian Putri Asriati T (Journal Publicuho, 2024)
This study aims to determine the Strategy of the Investment Service and One-Stop Integrated Service in Increasing Investment in Kendari City. The research was conducted using qualitative descriptive research. The informants in this study are as follows: Secretary of the One-Stop Integrated Investment Service Office, Head of the One-Stop Integrated Investment Service Division, Head of the One-Stop Integrated Investment Service Determination Division, Young Expert Policy Analysis/Head of Investment Climate Development Section\IMB Technical Team, Investment Data Processor. Thus, the total number of informants is 5 people. The results of the study show that the strategy implemented by the Kendari City DPMPTSP in increasing investment has included comprehensive efforts through simplifying licensing, promoting regional potential, and improving one-stop services. Good strategic planning and supporting regulations, such as the Investment Law and the Job Creation Law, have become important foundations for creating investment certainty. Partnerships with various parties and developing human resource capacity have also strengthened the quality of DPMPTSP services. Although it has not fully achieved the investment target, the realized investment contribution significantly impacts the local economy, including job creation, increasing purchasing power, developing MSMEs, and infrastructure development.